2019
DOI: 10.1002/pld3.194
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis thaliana N‐recognin E3 ligase PROTEOLYSIS1 influences the immune response

Abstract: N‐degron pathways of ubiquitin‐mediated proteolysis (formerly known as the N‐end rule pathway) control the stability of substrate proteins dependent on the amino‐terminal (Nt) residue. Unlike yeast or mammalian N‐recognin E3 ligases, which each recognize several different classes of Nt residues, in Arabidopsis thaliana, N‐recognin functions of different N‐degron pathways are carried out independently by PROTEOLYSIS (PRT)1, PRT6, and other unknown proteins. PRT1 recognizes type 2 aromatic Nt‐destabilizing resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…In a recent study in Arabidopsis, it was demonstrated that loss of function of PRT1, involved in N-degron pathways of ubiquitin-mediated proteolysis, improves the plant immune system. DMR6 and DLO1 proteins were accumulated in the former study indicating their importance in regulating the basal defense system 77 .…”
Section: No Responsive Tfs Play Role In Diverse Physiological Processmentioning
confidence: 78%
“…In a recent study in Arabidopsis, it was demonstrated that loss of function of PRT1, involved in N-degron pathways of ubiquitin-mediated proteolysis, improves the plant immune system. DMR6 and DLO1 proteins were accumulated in the former study indicating their importance in regulating the basal defense system 77 .…”
Section: No Responsive Tfs Play Role In Diverse Physiological Processmentioning
confidence: 78%
“…Plants with a prt6 loss-of-function allele exhibit increased resistance to bacterial pathogens in both barley and Arabidopsis (109). Similarly, a prt1 loss-offunction allele shows enhanced bacterial resistance in Arabidopsis (110). Loss of either E3 results in a constitutive increase in defense proteins, creation of a "primed" defense state normally only observed in wild-type leaves after infection of other leaves, and increased synthesis of other defense metabolites (110,109).…”
Section: Prr Immune Receptors With Fls2 As a Paradigmmentioning
confidence: 99%
“…Similarly, a prt1 loss-offunction allele shows enhanced bacterial resistance in Arabidopsis (110). Loss of either E3 results in a constitutive increase in defense proteins, creation of a "primed" defense state normally only observed in wild-type leaves after infection of other leaves, and increased synthesis of other defense metabolites (110,109). PRT6 modulates the stability of a family of transcription factors that regulate the hypoxic responses to pathogens that induce undifferentiated cell growth, such as cysts or galls (111).…”
Section: Prr Immune Receptors With Fls2 As a Paradigmmentioning
confidence: 99%
“…ERFVII group was the first substrate of the PCO branch of the PRT6 N-degron pathway described in plants ( Gibbs et al , 2011 ; Licausi et al , 2011 ) followed by the transcriptional regulators polycomb repressive complex 2 subunit VERNALIZATION 2 (VRN2) ( Gibbs et al , 2018 ) and LITTLE ZIPPER 2 (ZPR2) ( Weits et al , 2019 ). N-degron pathway substrates regulate important aspects of plant development such as seed storage mobilization ( Zhang et al ., 2018 a , b ), germination ( Holman et al , 2009 ; Gibbs et al , 2014 ), photomorphogenesis ( Abbas et al , 2015 ), stomatal closure ( Gibbs et al , 2014 ), shoot and leaf development ( Graciet et al , 2009 ), root architecture ( Shukla et al , 2019 ), SAM function ( Weits et al , 2019 ), vernalization ( Gibbs et al , 2018 ; Labandera et al , 2020 ), flowering ( Vicente et al , 2017 ), or leaf senescence ( Yoshida et al , 2002 ), and also regulates stress responses such as flooding ( Hartman et al , 2019 ) or pathogen attack ( de Marchi et al , 2016 ; Vicente et al , 2019 ; Till et al , 2019 ).…”
Section: Nitric Oxide and Hypoxic Stress Crosstalkmentioning
confidence: 99%